2023
DOI: 10.1093/jxb/erad295
|View full text |Cite
|
Sign up to set email alerts
|

LESION MIMIC MUTANT 1 confers basal resistance to Sclerotinia sclerotiorum in rapeseed via a salicylic acid-dependent pathway

Abstract: Rapeseed (Brassica napus) is a major edible oilseed crop consumed worldwide. However, its yield is seriously affected by infection from the broad-spectrum non-obligate pathogen Sclerotinia sclerotiorum due to a lack of highly resistant germplasm. Here, we identified a Sclerotinia-resistant and light-dependent lesion mimic mutant from an EMS-mutagenized population of the rapeseed inbred Zhongshuang 11 (ZS11) named lesion mimic mutant 1 (lmm1). The phenotype of lmm1 is controlled by a single recessive gene, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The RBOH gene family encode for membrane proteins that function in plant development and stress responses including the production of reactive oxygen species associated with MAMP-recognition and stomatal closure [40][41][42]. Recent studies in rapeseed (Brassica napus) proposed a model whereby resistance to sclerotinia involves hydrolysis of the pathogen's cell wall by host-derived glucanases and defence activation via RBOHF-oxidases [43]. The molecular basis of kiwifruit resistance to sclerotinia is poorly understood; however, it is possible that the stronger expression of PR2 and RBOHF in 'Zesy002 and 'Hayward', compared with 'Hortgem Tahi', may partly explain their relative differences in resistance to foliar infection by S. sclerotiorum.…”
Section: Discussionmentioning
confidence: 99%
“…The RBOH gene family encode for membrane proteins that function in plant development and stress responses including the production of reactive oxygen species associated with MAMP-recognition and stomatal closure [40][41][42]. Recent studies in rapeseed (Brassica napus) proposed a model whereby resistance to sclerotinia involves hydrolysis of the pathogen's cell wall by host-derived glucanases and defence activation via RBOHF-oxidases [43]. The molecular basis of kiwifruit resistance to sclerotinia is poorly understood; however, it is possible that the stronger expression of PR2 and RBOHF in 'Zesy002 and 'Hayward', compared with 'Hortgem Tahi', may partly explain their relative differences in resistance to foliar infection by S. sclerotiorum.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments reveal that after infection with S. sclerotiorum, BnaNPR1 transgenic plants activate the expression of genes related to the SA defense response [36]. Recently, Yu et al [27] found a lesion to mimic mutant of rapeseed confers basal resistance to S. sclerotiorum via an SA dependent pathway. All these studies validate that SA plays an important role in resistance to S. sclerotiorum.…”
Section: Discussionmentioning
confidence: 99%
“…3.6. SsShy Was Required for the Virulence of S. sclerotiorum SA plays an important role in host resistance during the interaction between S. sclerotiorum and plants [24][25][26][27]. To determine whether SsShy1 is related to the virulence of S. sclerotiorum, we inoculated mycelium plugs of ∆Ssshy1, ∆Ssshy1/SsShy1 and the wild type onto detached leaves of B. napus.…”
Section: Deletion Of Ssshy1 Increased Sensitivity To Exogenous Samentioning
confidence: 99%
See 1 more Smart Citation
“…The release of several reference genomes, such as Darmor v4.1 and v10 (Chalhoub et al ., 2014 ; Rousseau‐Gueutin et al ., 2020 ) and ZS11.v0, v10 and v2 (Chen et al ., 2021 ; Song et al ., 2020 ; Sun et al ., 2017 ), and the application of SNP chips (Edwards et al ., 2013 ; Li et al ., 2023a ; Xiao et al ., 2021 ) in rapeseed provide opportunities for discovering key genes controlling silique number in rapeseed. In addition, several QTL mapping methods have been developed for identifying candidate genes associated with important agronomic traits in rapeseed, such as natural‐population‐based GWAS (He et al ., 2017 ; Khan et al ., 2021 ), transcriptome‐wide association analysis (TWAS) (Tan et al ., 2022 ; Tang et al ., 2021 ) and parental‐population‐based linkage analysis methods such as bulked segregant RNA sequencing (BSR) (Fu et al ., 2019 ) and bulked segregant analysis (BSA) (Wang et al ., 2016 ; Yu et al ., 2023 ; Zhao et al ., 2020 ). Databases built upon these data, such as A Gene Expression Database for Brassica Crops (BrassicaEDB, https://brassica.biodb.org/ ) (Chao et al ., 2020 ), qPCR Primer Database (qPrimerDB, https://qprimerdb.biodb.org/ ) (Lu et al ., 2018 ), Brassicaceae Database (BRAD, http://www.brassicadb.cn/#/ ) (Chen et al ., 2022 ) and Brassica napus multi‐omics information resource (BnIR, https://yanglab.hzau.edu.cn/BnIR ) (Yang et al ., 2023 ), provide important data resources and analysis platforms for genetic breeding research in rapeseed.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%